Significance of determination of hemodynamic phenotypes in early diagnosis of cardiovascular disorders in children with diabetes mellitus - H. O. Lezhenko; O. Ye. Pashkova; K. V. Samoilyk (Patologìâ)
Aim. To stratify hemodynamic phenotypes in children with diabetes mellitus and their frequency, depending on the duration of the disease.